Promotion of Tax Culture through Tax Advisory Centers: Impact of the NAF over the Recaudation and the Knowledge of the Machala Canton - Crespo García, Marjorie Katherine; Romero Lalangui, Martin Andres (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
This study analyzes the results achieved by the NAF project of the UMET Machala on the strengthening of the taxation culture from the taxpayers of the territory, and its academic and fundraising effects. A descriptive methodology was applied, with a quantitative approach and a longitudinal cut, through the descriptive analysis of the registry of 4,690 people attended and 124 surveys of trained participants. The results show that the project activities positively impacted the recognition of fiscal responsibilities of micro-entrepreneurs, increasing the cantonal revenue, in addition to the knowledge generated, which supposed a contribution to the academy and the society.